The Paradoxical Identity of Chinese Speech-Language Pathologists in the Clinical Practice Context of Pediatrics - Xiuxiu Shen; Shuai Zhang; Bingqing Nie; Yanxiang Wang; Lu Liu; Wen Ma (SAGE Open)
The profession of SLPs in China has garnered escalating interest across diverse sectors of society. However, there is a lack of research concerning exploring their professional identity. This study aims to depict the current status and specific manifestations of the professional identity of Chinese SLPs through in-depth interviews. This study employed a qualitative research method, specifically utilizing content analysis. In-depth one-on-one face-to-face interviews were conducted with 28 Chinese SLPs. Subsequently, the analysis of the data involved categorizing interview content into main themes and subthemes following established research protocols. This systematic approach facilitated a comprehensive exploration of the professional identity of SLPs. Through a detailed analysis of the interview content, we delineated the current status and distinct manifestations of the professional identity of SLPs. This exploration yielded five main themes, including career motivations, occupational cognition, sense of belonging, occupational stress and challenges, and future career planning, and 13 subthemes. The professional identity of Chinese SLPs demonstrated multifaceted attributes. They navigated between the desire for social recognition, the quest for high-quality career advancement prospects, and the challenge of unsatisfactory working conditions. This juxtaposition reflected a blurred state of both professional identity and non-identity. The intricacy of this dynamic was intricately linked to the developmental stage and distinctive characteristics of the speech-language therapy sector in China, further shaped by the influences of unique cultural backgrounds.